IMPACT OF CAPITAL STRUCTURE ON CORPORATE ACTION BENEFITS TO SHAREHOLDERS - Dr M P Pandikumr, Mr.Bharath Rajesh, Dr Ananth (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research paper examined the impact of capital structure on corporate action benefits to shareholders. Debt-Equity ratio was used as the independent variable to represent capital structure. Return on Equity, Operating Margin, Earnings per share, Dividend per share and financial leverage were the dependent variables used. 15 Listed Public companies (on the basis of market capitalization) from three industry sub-sectors which contributes to 88% of the total industry contribution to the country’s GDP was analysed from the data collected for a period of 8 years from 2011-12 to 2018-19. The study found that the impact of capital structure is not strong but subtle enough to influence corporation action benefits shareholders (EPS & DPS) when we consider the whole of the three sub-sectors chosen for study. But when considered individually construction sub-sector is hugely influenced by capital structure where debt-equity ratio has strong positive correlation with operating margin and degree of financial leverage. The level of dividend paid to shareholders is also significantly affected by capital structure in construction sub-sector. However, in the other two sub-sectors chosen viz. manufacturing and utility services the impact of capital structure is not significant on corporate action benefits to shareholders.